The Emotional Bonds Aspect of Religious Tourism Development in Baiturahman Grand Mosque - Safitri, Ulia; Ginting, Nurlisa; Marisa, Amy (Jurnal Koridor, 2023)
Tourism is highly dependent on the attractiveness and interest of tourists and local people to visit these destinations. When tourism is linked to the success of a city in supporting its economy, questions will arise about who has an emotional attraction to tourist destinations and what is the comparison between the levels of visits by local and foreign tourists to tourist destinations, especially religious tourism. The existence of an emotional bond between tourists and tourist destinations will help the level of visits that occur in the future. By using an emotional bond approach between visitors and religious tourism destinations, a comparison of the level of visits by local and foreign tourists will arise, so this problem becomes a complex matter to discuss. One of the tourist destinations that is experiencing regional development is the Baiturrahman Grand Mosque, Banda Aceh City, which is better known as religious tourism. In addition, this area has a very high level of visits, caused by changes and developments in the region. Therefore, this study aims to find the level of comparison of the number of visits by local and foreign tourists through the emotional ties of visitors and what factors can encourage tourists' desire to visit. The method used in this study is a mixture of qualitative and quantitative data obtained from literature studies, distributing questionnaires, field observations, and interviews; distributing questionnaires to 100 respondents, namely tourists and the surrounding community; conducting field observations at the research location; and conducted in-depth interviews with eight key informants, namely local community leaders, tourism practitioners, government officials, and academics. It will be analyzed using a qualitative descriptive method to produce comparative findings through the data obtained. This literature review can be applied by stakeholders as an evaluation tool in developing tourism, especially religious tourism in an area.